TYPES OF QUESTIONS ASKED BY ENGLISH TEACHERS IN TEACHING AND LEARNING PROCESS AT SMA PEMBANGUNAN UNP PADANG - Khairatul Ummah; Rusdi Thaib; Saunir Saun (Journal of English Language Teaching, 2016)
The purposes of this research are (1) To describe types of questions asked by teachers in teaching and learning process, (2) To know what language used by teachers in teaching English. This research is descriptive research. Object from this research are two English teachers at SMA Pembangunan Laboratorium UNP Padang. The data collection used two instruments are  audio recording and note taking. The data from this research  are questions asked by teacher based on suggested by Wanjryb (1992). From this research, researcher found that open ended questions are mostly occur in the classroom beside ; yes/no questions, short answer questions, display questions, referential questions and non retrieval questions. During research, there are three kind of languages that used by teachers are English, mixed English –Indonesian, and Indonesian.